Data on systematic review and meta-analysis of epidemiologic evidence on the association between perineal use of talc powder and risk of ovarian cancer - Taher, Mohamed Kadry (Data Brief, 2020)
This paper describes data from a systematic review and meta-analysis [1] conducted to identify and evaluate published peer reviewed evidence on the association between perineal use of talc powder and risk of ovarian cancer. These data were collected from multiple electronic bibliographic databases, as well as from grey literature sources, without applying time, language or other filters. A meta-analysis was conducted to quantitatively assess the ovarian cancer risk in relation to talc use and other potential risk factors.